Face-To-Face Or Online Speaking Practice: A Comparison of Students’ Foreign Language Classroom Anxiety Level - Rahmati Putri Yaniafari; Ajeng Ayu Rihardini (JEELS (Journal of English Education and Linguistics Studies), 2021)
Speaking using foreign language in front of other people can be one of the most anxiety-provoking situations. Learners who does not enjoy interacting with other people or being the center of attention may exhibit extreme anxiety when they are asked to take parts in oral presentation, discussion, or any other kind of language activities. A study found that online discussion may decrease the effect. It provides a non-threatening situation for learners who are shy and withdrawn. This survey study aims to see whether it is also applied in Indonesian tertiary education by investigating and comparing the learners' level of anxiety in face to face speaking class before Covid-19 pandemic and online speaking class during the pandemic. 120 students who experienced both speaking courses before and during the pandemic participated in the survey. Consistent with the result of other studies, this study found that in average, learners feel less anxious during during online speaking class (48,41%) compare to face-to-face class (60,96%).